In vitro cytotoxicity of four calcium silicate-based endodontic cements on human monocytes, a colorimetric MTT assay - Sedigheh Khedmat (Restorative Dentistry & Endodontics, 2014)
Objectives This study was performed to evaluate the cytotoxicity of four calcium silicate-based endodontic cements at different storage times after mixing.